Role And Impact Of Empowerment Programand Family Welfare Towards The Economic Welfare Of Residents Of Sei Kera Hilir II Village Medan City - Ahmad Nizar Mohammad Syamwil; Muhammad Anshar (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
This study examines the concept of empowerment in Islam, welfare from an Islamic perspective, and the role of the Family Welfare Empowerment Movement (PKK) in improving the economic welfare of residents in Sei Kera Hilir II Subdistrict, Medan. The concept of empowerment in Islam emphasizes efforts to strengthen individual and community capacities through independence, productivity, and social responsibility. Islamic teachings encourage empowerment by developing human potential, providing opportunities for self-reliance, and fostering cooperation in achieving social welfare. Welfare in Islam is understood as a holistic condition that includes material, spiritual, and social fulfillment, both in this world and the hereafter. The findings indicate that the PKK has played an important role in community empowerment through various programs, including skills training, entrepreneurship development, health promotion, educational support, environmental sustainability, and family welfare improvement. Several successful empowerment initiatives have enabled residents to develop home industries, handicraft businesses, food processing enterprises, and other income generating activities that contribute to family economic resilience. Furthermore, PKK activities have enhanced community participation, strengthened social solidarity, and improved awareness of health, education, and environmental management.